The Roy Bedichek family letters - Bedichek, Roy, 1878-1959 (University of North Texas Press, 1998)
Reading The Roy Bedichek Family Letters once again allows us to delve into rare vintage Bedichek. The collection reminds us what talent he had for describing the world around him, and for expressing his opinion of that world, but they also reveal his interest and involvement in his children's lives and his sense of humor in dealing with them, with his pets, and with the wildlife he became famous for observing.